DESCRIPTION OF STRESS IN COLLEGE STUDENTS ONLINE GAMBLING PERPETRATOR - Wajdi, Khaerul; Ariyanto, Mustaqim Setyo (Universitas Dharmawangsa Medan, 2025)
Technological developments are so rapid, one of the effects of technological and internet advances is online gambling which can cause addiction and difficulty in self-control, thus triggering stress as a reaction to the imbalance between individual demands and abilities. This study aims to determine the picture of stress in online gambling students. The research participants were 2 students involved in playing online gambling. The research method uses a qualitative approach with a phenomenological method, which aims to understand the subjective experiences of students who experience stress due to their involvement in online gambling. The results of the study showed that online gambling students experienced stress that had physical impacts such as insomnia and fatigue, as well as psychological ones such as anxiety, despair, and withdrawal from the social environment. This stress also interferes with their mental well-being and academic activities.